James K. Polk. - Sellers, Charles, 1923- (Princeton legacy library., 2015)
This definitive biography of James K. Polk, the second of three projected volumes, covers the most important years of Polk's political career-from a twice-defeated gubernatorial candidate in Tennessee to dark-horse candidate for the presidency and one of the most successful first eighteen months of any American president. The months of Polk's administration covered here contain the bulk of his expansionist program-the annexation of Texas, the settlement of the Oregon boundary with Great Britain, and the war with Mexico that led to the acquisition of California and New Mexico. This period also covers the first session of the 29th Congress, which produced under Polk's guidance the most important domestic legislation of any Congress of the century.Originally published in 1966.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.